Surface Characterization of TiNi Deformed by High-pressure Torsion - Awang Shri, Dayangku Noorfazidah; Tsuchiya, Koichi; Yamamoto, Akiko (ELSEVIER, 2014)
Effect of grain refinements and amorphization by high-pressure torsion (HPT) on surface chemistry was investigated on TiNi. X-ray diffraction and micro-Vickers tests were used to check the phase changes and hardness before and after HPT. X-ray photoelectron spectroscopy was used to observe the changes in the natural passive film formation on the surface. Phase analysis reveals the change of crystalline TiNi to nanostructured one with increased hardness with straining by HPT. Grain refinement and amorphization caused by HPT reduce the amount of metallic Ni in the passive films and also increase the thickness of the film.